Development of High-Efficiency n-Type Front and Back Contact Passivated Emitter and Rear Locally Diffused Solar Cells Using Atmospheric Pressure Chemical Vapor Deposition of Phosphosilicate Glass and Laser Processing - Yan, Xia (WILEY-V C H VERLAG GMBH, 2020)
10.1002/pssa.202000117